2016
DOI: 10.1007/s13277-015-4780-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA repair and xenobiotic pathway gene polymorphisms with genetic susceptibility to gastric cancer patients in West Bengal, India

Abstract: Gastric cancer is one of the most common malignancies in India. DNA repair gene or xenobiotic pathway gene polymorphisms have recently been shown to affect individual susceptibility to gastric cancer. Here, the possible interaction between common polymorphisms in X-ray repair cross complementing group I (XRCC1) gene and glutathione S-transferase (GST) genes (GSTM1, GSTT1 and GSTP1), smoking and alcohol consumption and overall survival in gastric cancer patients were evaluated. In this population-based case con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…47 Contrary to the results of the present study, some previous studies from North India have reported an increased risk with AA genotype of XRCC1p.Arg399Gln polymorphism in lung cancer, 48 head and neck cancer, 49 colorectal cancer 50 and prostate cancer. 51 Similarly, some studies from South India reported an association of increased risk with the AA genotype in gastric cancer, 52 colorectal cancer, 29 lung cancer, 53,54 cervical cancer, 55 Naso-pharyngeal cancer, 56 acute lymphoblastic leukemia 57 and acute myeloid leukemia. 58 However, few studies from South India reported no association of XRCC1p.…”
Section: Discussionmentioning
confidence: 98%
“…47 Contrary to the results of the present study, some previous studies from North India have reported an increased risk with AA genotype of XRCC1p.Arg399Gln polymorphism in lung cancer, 48 head and neck cancer, 49 colorectal cancer 50 and prostate cancer. 51 Similarly, some studies from South India reported an association of increased risk with the AA genotype in gastric cancer, 52 colorectal cancer, 29 lung cancer, 53,54 cervical cancer, 55 Naso-pharyngeal cancer, 56 acute lymphoblastic leukemia 57 and acute myeloid leukemia. 58 However, few studies from South India reported no association of XRCC1p.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, previous studies have reported that many environmental and lifestyle factors could contribute to the risk of developing gastric cancer, such as consumption of preserved food containing carcinogenic nitrates, tobacco smoking, alcohol consumption, and overweight (Alberts et al, 2003). In additional, previous studies have reported that some genetic factors may contribute to the risk of developing gastric cancer, such as miRNA-196a-2, stromelysin-1 promoter gene, DNA repair and xenobiotic pathway gene, TP53 condon 72 gene and cytotoxic T-lymphocyte antigen 4 gene (Krishnaveni et al, 2015;Tang et al, 2015;Zha et al, 2015;Ghosh et al, 2016;Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have reported on the association between XRCC1 polymorphisms and development of several types of cancers, including non-small cell lung cancer, gastric cancer, cervical cancer, hepatocellular carcinoma, pancreatic cancer, ovarian cancer, colorectal cancer, and thyroid cancer (Liu et al, 2012;Abdel-Fatah et al, 2013;Feng et al, 2014;Wang and Ai, 2014;Xia et al, 2014;Cătană et al, 2015;Han et al, 2015;Huang et al, 2015;Xu et al, 2015;Zhao and Chen, 2015;Ghosh et al, 2016). Liu et al (2015) observed a significant relationship between the XRCC1 Arg399Gln polymorphism and risk of cervical cancer in a meta-analysis comprising 2051 cervical cancer patients and 2919 control subjects.…”
Section: Discussionmentioning
confidence: 99%